The impact of different sources of science and technology finance on the innovation capability of high-tech industries in China - Haixin, Yuan; Hernandez, Alexander A. (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of science and technology (S&T) finance inputs on the innovation capability of China’s high-tech industries. Using panel data from 30 Chinese regions (2013–2022), the research employs the Entropy Weight-TOPSIS method to measure innovation capability and a fixed-effects model to analyze four financing channels: government funding, bank loans, venture capital, and capital market financing. Results show that all channels positively influence innovation, with capital market financing having the strongest effect (coefficient: 1.309), followed by government funding (0.514), venture capital (0.153), and bank loans (0.009). Regional disparities highlight higher innovation capability in eastern China. The findings suggest optimizing S&T finance policies to enhance innovation, emphasizing capital markets for mature firms and government support for early-stage ventures.